Penicitone: structural reassignment of a proposed natural product acid chloride - Novitskiy, Ivan M. (2024)
The proposed structure for the natural product penicitone, which contained a chemically improbable acid chloride functional group, was reassigned to a more probable structure using a combination of chemical knowledge, computer-assisted structure elucidation, and DFT methods.